2020
DOI: 10.1080/09638237.2020.1714010
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Common-Sense model of illness representations to explore children’s perceptions of, and coping with ADHD

Abstract: Background: Attention Deficit Hyperactivity Disorder (ADHD) among children is associated with difficulties in everyday functioning. According to the Common-Sense Model of Illness Representations (CSM), individuals' beliefs about their illness condition guide their attempts to cope with it. The model suggests five dimensions of illness representations: beliefs regarding the identity of the symptoms, its duration, causes, consequences, and one's ability to achieve control over it. Aims: The study aimed to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Just as our study demonstrated illness representation characteristics aligned with adolescents' description of functional seizures, Ringer (2021) found the characteristics to reflect the beliefs of adolescents with attention deficit hyperactivity disorder. Ringer (2021) also inductively identified an additional theme, uniqueness , that captured additional condition beliefs not included in the original five characteristics. Several responses from adolescents with functional seizures in our study could have been coded under the theme of uniqueness, or how functional seizures make them different from other adolescents.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Just as our study demonstrated illness representation characteristics aligned with adolescents' description of functional seizures, Ringer (2021) found the characteristics to reflect the beliefs of adolescents with attention deficit hyperactivity disorder. Ringer (2021) also inductively identified an additional theme, uniqueness , that captured additional condition beliefs not included in the original five characteristics. Several responses from adolescents with functional seizures in our study could have been coded under the theme of uniqueness, or how functional seizures make them different from other adolescents.…”
Section: Discussionsupporting
confidence: 59%
“…Deacon's (2023) qualitative study among adolescents with type 1 diabetes highlighted the importance of considering adolescents' developmental stage, namely identity development, when investigating their illness representations versus that of adults. Illness representations have been explored among children and adolescents with not only type 1 diabetes (Deacon, 2023;Huston & Houk, 2011), but also sickle cell disease (Huston & Houk, 2011), attention deficit hyperactivity disorder (Ringer, 2021), dental caries (Nelson et al, 2019), asthma (Tiggelman et al, 2014), inflammatory bowel disease (Silva et al, 2018), and chronic fatigue syndrome (Gray & Rutter, 2007). Researchers have also explored illness representations among adolescents and young adults with anxiety and depression, finding a strong emphasis on personal and treatment control of their mental health (Bear et al, 2021).…”
mentioning
confidence: 99%
“…During adolescence, the relationship between adolescents and parents may be conflicted, because of adolescents' desire for autonomy from parents and the demands for more responsibility (Almeida et al, 2013), and the fact that the presence of a chronic illness tends to hinder these developmental changes (Miller, 2018). However, the family environment is an important factor in the self‐management process of a chronic illness and may influence either the development of adolescents' illness representations or the adherence and well‐being of adolescents with T1D (Grey et al, 2015; Ringer, 2021). In fact, communication patterns, support, and health beliefs within the family environment shape adolescents' illness representations, which influence their emotional and behavioral responses to diabetes management, which in turn impacts diabetes outcomes (Broadbent et al, 2015).…”
Section: Introductionmentioning
confidence: 99%